IMPLEMENTATION OF CULTURAL 5R (RINGKAS, RAPI, RESIK, RAWAT & RAJIN) WITH SNI ISO 22000: 2009 APPROACH AND ASSESSMENT IN PT.Y SURAKARTA - Siti Rachmawati; Seviana Rinawati; Iwan Suryadi; Maria Paskanita (Universitas Darussalam Gontor, 2018)
SNI ISO 22000 standard is a mandatory standard for companies in the field of food for food safety systems. In its fulfillment, the 5R culture (Ringkas, Rapi, Resik, Rajin & Rawat) is implemented in PT.Y Surakarta with the aim of obtaining safely, healthy and productively so that work accidents can be controlled and food products produced quality.Methods of this research was a descriptive research which describes about the application of 5R culture in PT. Y Surakarta. Culture 5R was one of the programs used for the implementation of SNI ISO 22000: 2009 on Food Safety System. Assessment was conducted in 11 sections with 82.33% accounting, 71.3% Engineering, 83.3% HRGAL, 70.17% packing, 81.53% procerument, 82.92% QC, 73, 17% RMU, 66.00% Satellite, 81.25% Sourcing, 85.37 parts supply chain, 75.13% warehouse.The conclusion of this research was 5R culture including one of the programs used for the implementation of SNI ISO 22000: 2009 on Food Safety System and there were 4 parts under the target namely engineering, packing, RMU and satellite. Preferably the under-targeted section was routinely socialized about 5R and improvements were made to the findings of the 5R audit. Keywords : 5R, SNI ISO 22000 : 2009